1997
DOI: 10.1086/517320
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Clinical Significance for the Common Arginine‐to‐Leucine Substitution at Codon 463 of the katG Gene in Isoniazid‐Resistant Mycobacterium tuberculosis in Singapore

Abstract: Correspondencewere intervening cannot be answered at present. The absolute proof sults can be obtained with extensive sample preparation and hybridization. of the etiologic role of any microorganism in respiratory infections in very difficult to produce, since the presence of the microorganism in the inflammatory focus can only exceptionally be docu-In our study, we could conclude that M. pneumoniae was responsible for 13.3% of lower respiratory tract infections (bronchopneumonia and lobar pneumonia) in childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…However, in previous studies, the mutation at codon 463 was found in 3 to 61% of INH-susceptible M. tuberculosis isolates (5,6,13,17,18,23). Also, it was found that the activity of catalase, a katG-encoded enzyme, did not differ among isolates having either Arg or Leu at codon 463 (21,22).…”
Section: Tuberculosis Isolates and Assessment Of Inh Resistancementioning
confidence: 88%
“…However, in previous studies, the mutation at codon 463 was found in 3 to 61% of INH-susceptible M. tuberculosis isolates (5,6,13,17,18,23). Also, it was found that the activity of catalase, a katG-encoded enzyme, did not differ among isolates having either Arg or Leu at codon 463 (21,22).…”
Section: Tuberculosis Isolates and Assessment Of Inh Resistancementioning
confidence: 88%
“…Though R463 is almost exclusively present in the katG gene in isoniazid-susceptible clinical isolates of M. tuberculosis from Europe and North America, the substitution R463L has been found in some clinical isolates that are weakly resistant to isoniazid (MIC !1 Ìg/ml) [9,12,15]. However, the significance of substitution R463L in conferring resistance to isoniazid is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of this mutation in wild-type M. tuberculosis by in vitro mutagenesis did not significantly affect the sensitivity to isoniazid [14]. Characterization of clinical isolates of M. tuberculosis from Singapore and China showed that the majority of isoniazid-susceptible strains contained R463L substitution suggesting that this mutation does not contribute to the resistance of M. tuberculosis to isoniazid [15].…”
Section: Introductionmentioning
confidence: 88%
“…A similar scenario was observed in studies defining the role of the katG gene in isoniazid resistance in M. tuberculosis. Members of our group and others have shown that the predominant alteration in katG is R463L, which is detected in both isoniazid-resistant and -susceptible isolates and hence is considered a polymorphism and an unreliable indicator of isoniazid resistance (11,13,27). Thus, it is imperative for all studies elucidating the molecular mechanisms of drug resistance in M. tuberculosis to include drug-susceptible isolates as controls.…”
Section: Ethambutol (Emb) [(Ssј)-22јmentioning
confidence: 99%